A call for standardization: Practice patterns and management of critical illness-related corticosteroid insufficiency in surgical intensive care units. Issue 9 (September 2021) - Huang, Chun-Sing; Miles, Travis; Thomas, Brice; Todd, S. Rob; Wilson, Chad T.; Suliburk, James
Highlights: Steroid insufficiency is frequently encountered in the trauma population (50-70%). This survey assessed current practice patterns regarding critical illness related corticosteroid insufficiency in level 1 trauma centers. Practice patterns are highly variable and few centers have protocols in place for the diagnosis and management of insufficiency. While most providers are treating steroid insufficiency for septic shock, few are assessing for adrenal insufficiency in the trauma population Abstract: Introduction: Critical illness-rlated corticosteroid insufficiency (CIRCI) is a known sequela of severe injury and illness, yet its diagnosis and management are challenging. We hypothesized that CIRCI has significant variability in its diagnosis and management within surgical intensive care units (SICUs). Our study aimed to assess the state of practice of CIRCI in the American College of Surgery Committee on Trauma (ACS COT) certified level 1 trauma centers. Methods: An 11-item questionnaire was developed based on a CIRCI literature search with expert input from medical endocrinology, acute care surgeons, and surgical intensivists to assess practice patterns of CIRCI. Prior to distribution, it was validated across 2 separate institutions by board-certified critical care surgeons. The questionnaire was distributed to trauma intensivists within level 1 trauma centers in Southeast United States and was open from April 2019 to January 2020. Results: A total of 56 responses were collected with a response rate of 70%. 72% of respondents indicated they evaluate or manage CIRCI on a weekly basis. In regards to the diagnosis of CIRCI, only 5% of respondents use a formal protocol and 32% do not use laboratory testing. While a majority of respondents (94%) use corticosteroids in septic shock, 67% of those surveyed have not implemented mineralocorticoids as part of the management. 83% of respondents indicated a knowledge gap exists in the therapeutic value of corticosteroids for hemorrhagic shock. Conclusions: This study demonstrates extreme variability in the diagnosis and management of CIRCI. In particular most providers acknowledge a knowledge gap in the diagnosis of CIRCI and the role of corticosteroids in hemorrhagic shock. Few providers are using adjunctive mineralocorticoids in septic shock, although recent level 1 evidence have shown a survival benefit. These responses reflect an opportunity for national improvement in the management of CIRCI.